Anthropometric Profile and Habits of Physical Activity of a Scho Ol Students Mapuches Rural Temuco, Chile [Perfil Antropométrico y Hábitos de Actividad Física de Estudiantes Mapuches de Una Escuela Rural de Temuco, Chile] - Herrera-Valenzuela, T (Asociacion Espanola de Dietistas-Nutricionistas, 2015)
Introduction: The nutritional status of children can be a predictor of health in adulthood element, the Mapuche population has a non-Mapuche population that increased prevalence of obesity in Chile. The aim of this study was to determine the anthropometric profile and physical activity habits of Mapuche students of a particular charter school in the rural of Temuco city. Material and Methods: The design is not experimental, descriptive, transversal, with a quantitative approach. The sample included all students of the educational establishment Mapuches (n=23), in both sexes. He underwent anthropometric assessment ISAK and total time physical activity was estimated by the International Physical Activity Questionnaire, short version in Spanish (IPAQ-A). To correlate the variables a partial correlation was used. Results: The students average about 35.4% of fat mass, muscle mass 34.1%, 11.4% of residual mass, 12% of bone mass, 7% of residual mass and somatotype 4.9-5.1-1.8 that meso-endomorph classified as balanced. Regarding the total time physical activity, students reach 2225.9 minutes/week, your energy expenditure is 9592.1 (METs/min/week) and stay seated equals 228.6 minutes per week, finally negative correlation was found between BMI and total time of physical activity. Conclusions: The students have a mostly standard anthropometric profile, but with a troubling obesity rate. His activity level is high, placing them as active subjects according to normative tables.